Efficacy of Panax ginseng supplementation on androgen deficiency rats via metabolomics and gut microbiota. (December 2021) - Lin, He; Zhao, Jiarui; Liu, Zhongying; Liu, Zhiqiang; Lin, Zhe
Graphical abstract: Highlights: Metabolomics and gut microbiota were integrated to investigate the antagonistic action on androgen deficiency of Panax ginseng. 22 possible endogenous biomarkers of androgen deficiency were identified. 16 endogenous biomarkers related to Panax ginseng regulation were identified. 7 gut microbiota markers with significant changes related to Panax ginseng regulation were identified. Abstract: Panax ginseng could promote testosterone production and ensure the normal function of androgens in some clinical cases as a medicine and nutritional supplement. The purpose of this work was to investigate the efficacy and way of action of Panax ginseng in the treatment of androgen deficiency rats. The male castrated rats were gavaged with Panax ginseng decoction for 10 weeks. Urine samples were analyzed for metabolites by UPLC-Q-TOF-MS, and feces were analyzed for changes in intestinal flora by 16sRNA high-throughput sequencing. The results showed that Panax ginseng could significantly antagonize the symptoms of weight gain, target tissue atrophy and serum hormone level decline caused by androgen deficiency. A total of 16 potential biomarkers were significantly altered after treatment in the metabolomics, which related to tryptophan metabolism, bile acid biosynthesis and steroid hormone biosynthesis. Based on the changes of intestinal flora, a total of 7 species with significant changes were found to be involved in the regulation of intestinal flora of androgen deficient rats by Panax ginseng. To conclude, our study verified the effect of Panax ginseng on androgen deficient rats, and explored its biological mechanism by metabolomics and gut microbiota metagenomics methods.